2017
DOI: 10.21037/jtd.2017.09.29
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-stroma ratio (TSR) in non-small cell lung cancer (NSCLC) patients after lung resection is a prognostic factor for survival

Abstract: These results demonstrated that the TSR is a new prognostic factor for NSCLC. Stroma-poor tumors were associated with longer disease-free period and better prognosis than were stroma-rich tumors in NSCLC patients. The TSR may contribute to the development of individualized treatment for NSCLC in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 26 publications
1
53
0
Order By: Relevance
“…We objectively quantified the positive rate of Col I by image analysis using ImageJ. In the current study, the Col I‐rich stroma group was defined if >50% of the tumor area showed specifically positive reaction for Col I . The distribution of patients according to the expression level of Col I is shown in Figure .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We objectively quantified the positive rate of Col I by image analysis using ImageJ. In the current study, the Col I‐rich stroma group was defined if >50% of the tumor area showed specifically positive reaction for Col I . The distribution of patients according to the expression level of Col I is shown in Figure .…”
Section: Methodsmentioning
confidence: 99%
“…In the current study, the Col I-rich stroma group was defined if >50% of the tumor area showed specifically positive reaction for Col I. 30 The distribution of patients according to YAMAZAKI ET AL.…”
Section: Histopathological Analysis and Evaluation Of The Associatimentioning
confidence: 99%
“…TSR assessment is easy, quick and without additional costs. Previous research demonstrated the prognostic value of the TSR in different types of invasive solid tumors, including breast cancer . Most of these studies validated a worse prognosis for patients with stroma‐high tumors.…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, by identifying the stroma present in cancerous tissue, scientists would be able to learn more about the progression of cancer and start early treatments targeting the tumor stroma. Interestingly, recent studies show that the tumorstroma ratio (TSR) derived from image analysis also potentially serves as an independent prognostic factor in many types of cancer [7,9,10]. However, much of such work was done manually.…”
Section: Introductionmentioning
confidence: 99%
“…However, much of such work was done manually. For example, human observers were used for visual estimation of TSR in a previous report [10], which is a tedious and time-consuming task and subject to human bias. Such estimation generally involves tumor image segmentation, which is a critical task in medical image processing.…”
Section: Introductionmentioning
confidence: 99%